A Versatile Annulation Route to Primary-Amino-Substituted Naphthyridine Esters - Chen, Jinhua; Xu, Zijin; Wang, Tao; Lyssikatos, Joseph P.; Ndubaku, Chudi O. (Synlett, 2014)
A straightforward four-step synthesis of primary-amino-substituted naphthyridine esters from commercially available cyanopyridines was described. The route makes use of a condensation reaction between pyridinyl acetates with N,N-dimethylformamide dimethylacetal (DMF-DMA) to form ortho-cyano vinylogous carbamates. These intermediates can undergo facile cyclization with ammonium acetate in acetic acid to generate the corresponding naphthyridine esters in good synthetic yields. The synthesis of primary-amino-substituted 7-azaquinoxaline was also described.
Keywords: naphthyridine; annulation; vinylogous carbamates; heterocycles; scaffold